The Möbius strip topology : history, science, and applications in nanotechnology, materials, and the arts /: history, science, and applications in nanotechnology, materials, and the arts. (2022) - Möbius, Klaus (Klaus G.); Plato, Martin; Savitsky, Anton
No abstract available